Molecular Genetics of Pediatric Orthopaedic Disorders - Wise, Carol A.; Rios, Jonathan J. (Springer New York : Imprint: Springer, 2015)
In the past two decades we have seen a surge forward in understanding the genetics and biochemistry underlying many pediatric orthopaedic disorders. A few projects have even progressed into the realm of clinical trials that are primarily aimed at controlling progressive disease. Meanwhile, genomic technology development has outpaced expectations and is enabling gene discovery for disorders that were previously intractable with traditional genetic methods. Included in this latter category are common disorders that display multigenic inheritance, sporadic disorders, and very rare conditions that are difficult to ascertain. Simultaneously, the study of pediatric orthopaedic disorders has been continuously refined and updated, highlighting a number of likely genetic conditions that are as yet unsolved. Molecular Genetics of Pediatric Orthopaedic Disorders updates researchers and clinicians on new developments of pediatric orthopaedic genetics. The chapters inform the audience on the revolution in new genomic methods, the impact this is having on potential study designs, and the potential to discover genetic causes of many unsolved orthopaedic conditions. Recent examples have been included of pediatric orthopaedic conditions, both rare and common, that are being solved with these new methods. The book also educates geneticists and pediatric orthopedic clinicians on our understanding of the biology of "classic" genetic diseases that were derived from prior genetic studies. Chapters include biobanks and strategies for studying very rare disorders, genes and pathways causing primordial dwarfism, notch signaling in congenital scoliosis, and more.